Copy of s12

Copy of s12 - -1 2 By the Schwarz inequality we therefore...

This preview shows pages 1–2. Sign up to view the full content.

Solutions to homework # 12. 1. Let f = 1 at rational points and - 1 at irrational points. Then f is real and bounded, and f 2 = 1 is Riemann integrable. But f itself is not integrable. Now suppose f 3 is Riemann integrable. Consider the function φ ( t ) := t 1 / 3 . This function is deﬁned and coninuous over all of IR. By Theorem 6.11, the function f = φ ( f 3 ) is therefore integrable. 2. Suppose f , g ∈ R ( α ). First let us prove that k f + g k 2 ≤ k f k 2 + k g k 2 . Using the Schwarz inequality , we have k f + g k 2 2 = Z b a | f + g | 2 = Z b a | f | 2 + 2Re Z b a f g dα + Z b a | g | 2 Z b a | f | 2 + 2 ± ± ± ± ± Z b a f g dα ± ± ± ± ± + Z b a | g | 2 Z b a | f | 2 + 2 ² Z b a | f | 2 ! 1 / 2 ² Z b a | g | 2 ! 1 / 2 + Z b a | g | 2 = ² ( Z b a | f | 2 ) 1 / 2 + ( Z b a | g | 2 ) 1 / 2 ! 2 = ( k f k 2 + k g k 2 ) 2 . So, k f + g k 2 ≤ k f k 2 + k g k 2 . Now replace f by f - g and g by g - h where h is an arbitrary function in R ( α ), to get k f - h k 2 ≤ k f - g k 2 + k g - h k 2 . 3. Let F ( x ) := xf 2 ( x ). Since f is continuously diﬀerentiable, so is F . By the Fundamental Theorem of Calculus, Z b a ( f 2 ( x ) + 2 xf ( x ) f 0 ( x ))dx = F ( b ) - F ( a ) = 0 and, since R b a f 2 ( x )dx = 1, we have R b a ff ( x ) f 0 ( x )dx =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: -1 / 2. By the Schwarz inequality, we therefore conclude 1 4 = ± ± ± ± ± Z b a xf ( x ) f ( x )dx ± ± ± ± ± ≤ ² Z b a | f ( x ) | 2 ! 1 / 2 ² Z b a | xf ( x ) | 2 dx ! 1 / 2 . (1) The equality holds in this inequality if and only if the integrands are proportional. That means f ( x ) = cxf ( x ) for some c 6 = 0, since f is not identically zero. All solutions to this diﬀerential equation have the form f ( x ) = de cx 2 / 2 , 1 where d is another nonzero constant. For such a function though we cannot have f (0) = f (1) = 0, so equality in (1) is impossible. Thus Z b a ( f ( x )) 2 dx · Z b a x 2 f 2 ( x )dx > 1 / 4 . 2...
View Full Document

This document was uploaded on 11/17/2010.

Page1 / 2

Copy of s12 - -1 2 By the Schwarz inequality we therefore...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online